2016
DOI: 10.1155/2016/4659358
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Liquefaction Time and Proteins Involved in the Improvement of Seminal Characteristics in Dromedary Camels (Camelus dromedarius)

Abstract: Semen was collected from six dromedary camels using artificial vagina during rutting season. Liquefaction of the viscous semen occurred in 23.89 ± 1.49 h. During liquefaction, proteins with molecular masses of 24.55 kDa and 22.07 kDa appeared in conjunction with the disappearance of intact 26.00 kDa protein after 18–24 h. These proteins were identified as β-nerve growth factors (β-NGFs) in liquefied camel semen. Guanidine-HCL improves the rheological characteristics of dromedary camel semen along with signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…In a previous study, complete liquefaction was observed at 23.89±1.49H varying from 18 to 41H without any enzyme treatment (Mal et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study, complete liquefaction was observed at 23.89±1.49H varying from 18 to 41H without any enzyme treatment (Mal et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Algunos investigadores aplicaron licuefacción mecánica, agitación 5 , agitación 12,13 , punción y pipeteo 14 y centrifugación 15 , últimamente, exposición a ultrasonido con éxito para eliminar viscosidad y mejorar la preservación enfriada a corto plazo del semen de dromedario 11 . Otros autores complementaron el diluyente de semen con diferentes enzimas a fin de eliminar viscosidad, uso de catalizadores de descomposición con peróxido de hidrógeno 16 , catalizadores de descomposición de carbohidratos de cadena larga 17,18 , enzimas proteolíticas 14,15,[19][20][21][22] . Avances recientes del análisis de semen asistido por computadora (ASAC) demostraron su capacidad para una estimación precisa de función espermática y heterogeneidad en comparación con la evaluación tradicional del semen 23 .…”
Section: Introductionunclassified
“…Elimination of semen viscosity is one of the major topics that gained considerable attention of camelidae reproduction researchers over the past recent years (Rateb et al., 2020). Among other postulations, presence of proteins in the seminal plasma has been suggested to contribute to camelides semen viscosity (Kershaw‐Young et al., 2013; Mal et al., 2016). In the present results, non‐purified (T 0 ) protease‐liquefied semen showed a marked improvement in post‐thaw sperm motility compared to that of control.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic liquefaction of camel semen, particularly by using proteolytic enzymes, has been considered the most effective for elimination of camel semen viscosity and improving motility and kinematics of spermatozoa (Kershaw‐Young et al., 2017; Mal et al., 2016; Monaco et al., 2016). Nevertheless, protease‐based semen liquefaction was recently reported to drastically affect sperm vitality, acrosome integrity and sperm cell surface glycocalyx pattern especially after exposure to the stress of freezing/thawing cycle (El‐Bahrawy et al., 2017; Rateb et al., 2019).…”
Section: Introductionmentioning
confidence: 99%